Patient perspectives of diabetes care in primary care networks in Singapore: a mixed-methods study - Lay Hoon Goh; Anna Szücs; Chiew Jiat Rosalind Siah; Monica A Lazarus; E Shyong Tai; Jose M Valderas; Doris Yee Ling Young (BMC, 2023)
Abstract Background Type 2 diabetes (T2D) remains an important chronic condition worldwide requiring integrated patient-centred care as advocated by the Chronic Care Model (CCM). The Primary Care Networks (PCNs) in Singapore organise general practitioners (GPs) with nurses and care coordinators to deliver team-based care for patients with chronic conditions. This study examined the quality of care in the PCNs as defined by the CCM from the patients' perspective. Methods This study followed a cross-sectional convergent mixed-method design with T2D patients across three PCN types (GP-led, Group, and Cluster). The Patient Assessment of Chronic Illness Care (PACIC, range 1-5) was completed by a convenience sample of 343 patients. Multivariate linear regression was performed to estimate the associations between patient and service characteristics and PACIC summary score. Twenty-four participants were purposively recruited for interviews on the experienced care until thematic saturation was reached. Quantitative and qualitative data were collected concurrently and independently. Integration occurred during study design and data analysis using the CCM as guidance. Quantitative and qualitative results were compared side-by-side in a joint comparison table to develop key concepts supported by themes, subthemes, and patients' quotes. Results The PACIC mean summary score of 3.21 for 343 patients evidenced that some have received CCM consistent care in the PCNs. Being younger and spending more time with the GP were associated with higher PACIC summary scores. PACIC summary scores did not differ across PCN types. The 24 patients interviewed in the qualitative study reported receiving team-based care, nurse services, good continuity of care, as well as patient-centred care, convenient access, and affordable care. Key concepts showed that integrated care consistent with the CCM was sometimes received by patients in the PCNs. Patient activation, delivery system design/decision support, goal setting/tailoring, and problem-solving/contextual counselling were sometimes received by patients, while follow-up/coordination was generally not received. Conclusions Patients with T2D from the Singapore Primary Care Networks received integrated care consistent with the Chronic Care Model, particularly in patient activation, delivery system design/decision support, goal setting/tailoring, and problem-solving/contextual counselling. Follow-up/coordination needed improvement to ensure higher quality of diabetes care.